Method on PAPR reduction in digital beam-forming - Lu LIU; Guoqing ZHAO (Tongxin xuebao)
Digital beam-forming technology is one of the key technologies in 5G communication.However,the high peak-to-average power ratio in digital beam-forming would make the power amplifier work in the nonlinear region.Nowadays,the solutions to the high peak-to-average power ratio,such as selected mapping,embedded side information selected mapping have some faults:the complexity is high,and the utilization of the bandwidth is low.A blind selected mapping method to reduce the high peak-to-average power ratio based on MUSIC algorithm was proposed.In this method,the side information was omitted,so the utilization of the bandwidth was improved.Simultaneously,the result of the peak-to-average power ratio reduction and the complexity is much more enhanced.